Neutralization of acid precipitation in Istanbul, Turkey - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 1997)
The issue of acid deposition and associated environmental problems has received special attention during recent decades and has been the subject of extensive research in North America and western Europe. But similar studies in developing countries are very limited due to technological and financial restrictions. In this work the chemical composition of precipitation in Istanbul is studied. Precipitation samples are obtained from Florya, Bahcelievler and Goztepe for the period of January 1996 - October 1996. The samples are analyzed for hydrogen, sulfate, nitrate ions in the initial phase of the period (January 1996 April 1996) and in the final phase (May 1996 - October 1996) three additional ions of calcium, ammonium and bicarbonate are analyzed with the other ions. Results reveal that majority of the cases have pH values greater than 5.6, implying that precipitation is neutralized by a mechanism. Measurements and estimations establish that the possible neutralization agents are calcium and ammonium ions. A negative correlation between the sulfate, nitrate deposition and precipitation intensity is found for low precipitation values but a similar condition is not observed for high values of precipitation. The seasonal investigations illustrate that the sulfate and nitrate depositions are high in heating season months and low in the other months, implying a positive relationship between the air pollution and acid deposition.
Keywords: acid rain; ion concentrations